Long-term functional outcome of sacrococcygeal teratoma in a UK regional center (1993 to 2006). - Tailor, J; Roy, P; Hitchcock, R; Grant, H; Johnson, P; Joseph, V; Lakhoo, K (2009)
BACKGROUND: Sacrococcygeal teratoma (SCT) is the commonest neonatal neoplasm. Its long-term effects are important in prenatal counseling and the delivery of an appropriate postoperative plan. AIM: To determine the long-term functional outcome after SCT excision in a UK regional center. STUDY DESIGN: Follow-up data for all patients with a SCT excised at the John Radcliffe Hospital in Oxford was collected retrospectively from notes and prospectively in clinic visits. OUTCOME MEASURES: Clinical evidence of bowel or bladder impairment, mortality. RESULTS: Over a 14-year period, 18 patients had a histologic diagnosis of SCT. Nine patients (50%) were born, 7 (39%) were terminated, and 2 (11%) were stillbirths. Of the 9 patients who had SCT resection, 4 (44%) were antenatally diagnosed. There were no perioperative deaths and alpha-fetoprotein levels normalized by 6 to 12 months after tumor resection. Median follow-up of patients was 30 months (range: 6 to 132 mo) with 1 patient lost to follow-up at 6 months, although he was asymptomatic at the time. Three patients developed urologic complications (2 within 1 year of tumor resection), including 2 patients with neurogenic bladder dysfunction and 1 patient with detrusor sphincter dyssynergia. CONCLUSIONS: Approximately one-third of patients will develop major urologic complications after resection of SCT. Routine ultrasonography in the first postoperative year after tumor resection may help to identify patients with neuropathic bladder at the early stage and predict late complications. Parents need to be aware of this potential long-term complication during prenatal counseling and the need for regular long-term follow-up with the pediatric surgical team.